- PENGARUH MEDIA LEGO TERHADAP KEMAMPUAN BERPIKIR LOGIS ANAK - Sri Mulyati (LPPM Universitas Muhammadiyah Cirebon, 2022)
This study aims to determine the effect of Lego media in improving the logical thinking ability of group B children at RA Nihayatul Amal Purwasari. In this study, the method used is a quasi-experimental type of research. The target of this research is group B RA Nihayatul Amal Purwasari. The subjects of this study were 26 students, consisting of 13 students in the experimental group and 13 students in the control group. The experimental group was given treatment with Lego media while the control group was given learning as usual. Instruments in data collection using observation sheets and documentation. The data obtained were then analyzed and tested by Wilcoxon and Mann Whitniey to determine the difference between the experimental group and the control group. The results obtained in this study indicate that there is an influence of Lego media on the logical thinking ability of children in group B at RA Nihayatul Amal Purwasari. The first hypothesis test is through the Wilcoxon Test on Asymp. Sig. (2-tailed) with a value of 0.034 and Mann Whitney Test on Asymp. Sig. (2-tailed) with a value of 0.016